2015
DOI: 10.1167/iovs.15-16712
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Pupillography Identifies Changes in Visual Sensitivity According to Severity of Diabetic Retinopathy in Type 2 Diabetes

Abstract: Asymmetry in local response delays measured by mfPOP may provide useful information regarding the severity of diabetic retinopathy and may have clinical use as a rapid, noninvasive method for identifying functional loss even in the absence of NPDR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 49 publications
(82 reference statements)
4
36
1
Order By: Relevance
“…Note that asymmetry adds the effects of hyper- and hypo-sensitivity across congruent regions in the two eyes. Asymmetries provided perfect performance (AUC = 1.0) for eyes with mild to moderate retinopathy25.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Note that asymmetry adds the effects of hyper- and hypo-sensitivity across congruent regions in the two eyes. Asymmetries provided perfect performance (AUC = 1.0) for eyes with mild to moderate retinopathy25.…”
Section: Discussionmentioning
confidence: 97%
“…We did not have and T2D subjects in this cohort who had mild/moderate non-proliferative retinopathy to determine if similar results are replicated. However other mfPOP studies from our lab have demonstrated sensitivity loss and response delays with progression to mild/moderate NPDR25. That study explicitly compared the diagnostic power of regions of sensitivity loss, hypersensitive regions, and the asymmetry between regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively recent advances in the understanding of the neural mechanisms that mediate the pupil response have greatly renewed interest in pupillometry as a tool for assessing retinal function in patients with acquired91011 and inherited12131415 retinal disease. That is, the afferent limb of the pupillary response to light is now thought to be driven primarily by intrinsically photosensitive retinal ganglion cells (ipRGCs) that contain the photopigment melanopsin1617.…”
mentioning
confidence: 99%
“…It tests both eyes concurrently in under 7 min using responses of the pupils. Its design makes it tolerant of senescent pupils and the macular test has high diagnostic power in early stage diabetes and AMD . The presence of slight hypersensitivities within these fields seems to predict which Wet‐AMD patient response to anti‐VEGF treatment .…”
mentioning
confidence: 99%